Organic synthesis - Smith, Michael B. (London, Academic Press, 2017)
Just looking at the first line, the setting is a place that$1 (Bs threatening to tip over into the unnatural. The uncanny atmosphere is eerily present, like something terrible you can$1 (Bt look away from, and in fact, want to read more of. Here$1 (Bs how the description achieves this: The juxtaposition of a tourist-like welcome and the death imagery that follows Very physical descriptions of (3z(Bunearthed bones(3y (Band (3z(Ba city thrumming(3y (BThings are given agency that shouldn$1 (Bt have agency: the city, dead children Intentions and desires are disconnected from people like bodies without a soul With carefully chosen language and imagery, the blurb transports us to a Buenos Aires that$1 (Bs teeming with the dead. It$1 (Bs what ties the short stories together. We don$1 (Bt need to know about individual characters or plot lines because the setting is described so intentionally, it makes us feel uncomfortable with our own curiosity for this dark place: what ungodly thing is happening in this city?s
Subject Index 1055-1080p.
Keywords: Pericyclic reactions; Synthetic strategies; Chemistry